Development of Asthma Mouse Model By Dermal Sensitization - Isameldin Abdalla; Amir A. Bashir (Sudan Journal of Medical Sciences)
Background: Urbanization is often associated with the increased asthma prevalence in recent times. Asthma prevalence in Khartoum, Sudan has risen to 18.2% among children aged 13–14 years. Extensive research has been done on the prevalence and triggering factors of asthma, however, no experimental research using animal models has been done. Thus, this study aims to develop asthma phenotype in mice with TDI sensitization. Methods: This study was a controlled experimental study in which 24 BALB/Lac mice were equally divided into control (G1) and treatment (G2) groups. G1 was treated with 25μL of 0.3% TDI in acetone olive oil (AOO) applied on the same days. Autopsy and samples (blood, bronchoalveolar lavage fluid [BALF], and lung tissue) collection were performed on day 12. Results were analyzed using t-test on the SPSS. Results: A statistically significant increase in neutrophils and eosinophils was observed in the blood of TDI-sensitized mice (G2) with a reduction in lymphocytes. In the TDI group, a significant increase was seen in the BALF, neutrophils, lymphocytes, and basophils; the increase in eosinophils and monocytes was nonsignificant. Besides, lung-related histopathological changes in the TDI group were hyperemia, leukocytic infiltration, thickening of bronchoalveolar walls, and damage of respiratory epithelium. Conclusion: TDI-sensitized mice showed a significant increase in granulocyte count, especially neutrophils and eosinophils, both in the blood and BALF with inflammatory and allergic lung tissue changes. These changes confirmed the allergic responses and the development of asthma phenotype.